IOT Based Wheeled Robotic Arm - V, Abhilash; K.Mani, P (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) is one major field which is fast developing now a days. The IoT means the connection or controlling of an equipment using internet. The another field everyone attracted is towards the robotics. Everyone wants to use a robot because they can do things what we can only imagine to do so. Here in this project we are blending the IoT with the robotics. The robot is controlled by the IoT here. The robot used here is the wheeled robot. Because it is easy to use a wheeled robot in a smooth and hard surface, and it is more energy efficient than the legged robot. The basic motive of the robot here is to pic and place an object from one place to another. This paper discuss about the pick and place wheeled robotic arm which is controlling using the Internet of Things. Â Â